Methods of tutoring activities in the training of computer science - Bariieva, Elvina; Toporkov, Tymofii (Ukrainian journal of educational studies and information technology, 2018)
The article emphasizes that in the conditions of the reform of the domestic system of education and the Conception of the New Ukrainian School it became possible to formulate an individual program of studying students of a secondary school. In this regard, the author resorts to the position of the teacher of computer science as a tutor, that is, a person who actualizes the educational needs of students, works with them, discusses them, and seeks to help the ward in their satisfaction. In the process of studying computer science tutor position is becoming relevant in profile education. The activity of the tutor in teaching computer science is based on the ideas of humanistic and personality-oriented and systemic approaches. Teutor's accompaniment of students at the computer science classes is to continuously stimulate the student's independent cognitive activity, the need for self-improvement and the development of research skills in information activities. On the basis of the analysis of scientific literature on the problems of tutor activity, the following methods of tutoring activity in the teaching of informatics are singled out: methods of practical orientation activity, methods of problem-based learning, method of projects, psychodiagnostic methods, methods of active learning, methods of analysis and self-analysis, binary methods, methods of distance learning, method portfolio scientists (T. M. Kovaleva, K. P. Osadcha) consider the most effective method of tutorial support as a method of portfolio, which is used at all stages (primary and adolescent) and at all stages of tutor's escort. In the process of tutorial support several types of portfolios can be used: thematic, presentation, portfolio of achievements.